1913
DOI: 10.1080/11035891309449550
|View full text |Cite
|
Sign up to set email alerts
|

Die radioaktiven Substanzen und die geologische Forschung

Abstract: o l a 3 ~~11igsreriniigen wie die rc-Stralilen, n-erden aber ron einer 5)))m clickan Aliuiiini~uii~~latte oder voii einer 1 w i i i dicken Bleiplntte einigerniassen rollstiindig absorbiert ; die 7-Strnhlen sind analog niit den starli dnrchdringenden l Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Zircon is not always completely crystalline, but commonly occurs in a partly or completely amorphous (metamict) state (Holland and Gottfried 1955;Chakoumakos et al 1987;Murakami et al 1991;Weber 1990) due to radiation damage resulting from e-decay events (Hamberg 1914;Ewing et al 1987;Weber 1993;Weber et al 1994). Average U concentrations in zircon vary from 5 to 4000 ppm, and average Th concentrations vary from 2 to 2000 ppm; thus, in periods of hundreds of…”
Section: Introductionmentioning
confidence: 97%
“…Zircon is not always completely crystalline, but commonly occurs in a partly or completely amorphous (metamict) state (Holland and Gottfried 1955;Chakoumakos et al 1987;Murakami et al 1991;Weber 1990) due to radiation damage resulting from e-decay events (Hamberg 1914;Ewing et al 1987;Weber 1993;Weber et al 1994). Average U concentrations in zircon vary from 5 to 4000 ppm, and average Th concentrations vary from 2 to 2000 ppm; thus, in periods of hundreds of…”
Section: Introductionmentioning
confidence: 97%
“…Metamict minerals were judged amorphous because of their conchoidal fracture and isotropic optical properties, but well developed crystal faces proved that they were originally crystalline. Hamburg 1914 was the first to suggest that metamictization is a radiationinduced phase transition caused by alpha decay of radionuclides in the U and Th decay series. X-ray diffraction studies confirmed that metamict minerals were either amorphous or very finely crystalline (e.g., Vegard 1916).…”
Section: Introductionmentioning
confidence: 98%
“…Metamictisation is defined as the amorphous state of a substance that has lost its periodic structure (Brøgger, 1893). Metamictisation is a radiation-induced, periodic-to-aperiodic phase transition caused by α-particles from the U or Th decay series (Hamberg, 1914). Damage by α-decay has two components that occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%